Influence of Constitutive Models on Cyclic Pore Pressure and Liquefaction Assessment in Srandakan, Bantul, Indonesia - Amalina, Anisa Nur; Makrup, Lalu; Saputra, Elvis (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2026)
Liquefaction potential in earthquake-hazard areas is correlated with earthquake-induced cyclic loading. This condition leads to an important selection in the constitutive soil model in numerical site response analysis. This study aims to evaluate the effect of different constitutive soil models on cycling pore pressure by using a numerical model. The case was taken in Srandakan, Bantul, Indonesia, which consists of sand and clay soil. A representative ground motion was derived from a probabilistic seismic hazard analysis, with PGA ≈ 0.31, in a one-dimensional dynamic analysis using PLAXIS 2D. Three constitutive models, Mohr–Coulomb (MC), Hardening Soil with small-strain stiffness (HSsmall), and PM4Sand, were compared in terms of excess pore pressure development and pore pressure ratio (Ru) evolution. The results showed that MC neglected a pore-pressure accumulation, while HSsmall captured only a limited nonlinear response. Meanwhile, PM4Sand predicted more significant cyclic pore pressure changes in sandy layers due to its state-dependent plasticity formulation. Nevertheless, Ru values remained well within acceptable limits at all depths, indicating that the applied seismic excitation did not trigger liquefaction. The findings demonstrated that model selection substantially affected pore pressure response in seismic liquefaction analysis.